Central Serous Retinopathy in A Male Patient with Takayasu Disease ? A Rare Presentation - Khabir Ahmad, Sharmeen Akram, Azam Ali (Pakistan Journal of Ophthalmology, 2010)
Takayasu disease is a rare large and medium vessel arteritis. It was reported by Dr Mikito Takayasu in 1908. It is more common in Asia especially in Japan where about 150 cases are reported per year1. The disease is reported all over the world with an incidence of 2.6 per million / year. The disease is more common among females. The ophthalmic vascular changes of Takayasu arteritis are described in the literature2-8 , and are related to hypoxic changes with involvement of the carotids and retinal artery stenosis. We report a rare atypical presentation of ocular Takayasu disease in a male patient which was successfully managed.